Development of a procedure for the production of oat-supplemented wheat bread - Thi Phuong Loan Huynh; Ngoc Han Phan; Thuy Bao Nhi Tran; Thi Truc Loan Bui (CTU Journal of Innovation and Sustainable Development)
Oat (Avena Sativa L.) is characterized by a high content of protein with a favorable amino acid composition, β-glucans, and unsaturated fatty acids. This study aimed to determine the factors affecting the physical properties and sensory value of bread made of wheat combined with oats. The research was to investigate the effects of (i) the proportion of added oat flour (15, 20, 30%); (ii) the fermentation time (60, 75, 90, 105 min); and (iii) baking temperature (200, 210, 220oC) for baking time (10, 15, 20 min) to bread quality with added oat flour. The quality assessment criteria include hardness, moisture content, specific volume, color, and sensory value of the product. According to the results, the most acceptable proportion of oat flour supplement in all of the criteria of bread was found to be 20%. The fermentation time of 90 minutes provided the best texture and highest sensory value for the bread. Oat-wheat bread was baked at 210oC for 20 minutes to obtain a good taste, helping the bread to have a crispy texture, smooth surface, and an attractive yellow-brown color.